Chaperone co‐inducer BGP‐15 mitigates early contractile dysfunction of the soleus muscle in a rat ICU model. (18th December 2019) - Cacciani, Nicola; Salah, Heba; Li, Meishan; Akkad, Hazem; Backeus, Anders; Hedstrom, Yvette; Jena, Bhanu P.; Bergquist, Jonas; Larsson, Lars
Abstract: Aim: Critical illness myopathy (CIM) represents a common consequence of modern intensive care, negatively impacting patient health and significantly increasing health care costs; however, there is no treatment available apart from symptomatic and supportive interventions. The chaperone co‐inducer BGP‐15 has previously been shown to have a positive effect on the diaphragm in rats exposed to the intensive care unit (ICU) condition. In this study, we aim to explore the effects of BGP‐15 on a limb muscle (soleus muscle) in response to the ICU condition. Methods: Sprague‐Dawley rats were subjected to the ICU condition for 5, 8 and 10 days and compared with untreated sham‐operated controls. Results: BGP‐15 significantly improved soleus muscle fibre force after 5 days exposure to the ICU condition. This improvement was associated with the protection of myosin from post‐translational myosin modifications, improved mitochondrial structure/biogenesis and reduced the expression of MuRF1 and Fbxo31 E3 ligases. At longer durations (8 and 10 days), BGP‐15 had no protective effect when the hallmark of CIM had become manifest, that is, preferential loss of myosin. Unrelated to the effects on skeletal muscle, BGP‐15 had a strong positive effect on survival compared with untreated animals. Conclusions: BGP‐15 treatment improved soleus muscle fibre and motor protein function after 5 days exposure to the ICU condition, but not at longer durations (8 and 10 days) when the preferential loss of myosin was manifest. Thus, long‐term CIM interventions targeting limb muscle fibre/myosin force generation capacity need to consider both the post‐translational modifications and the loss of myosin.